2011
DOI: 10.1155/2011/609601
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Complications Following Percutaneous Endoscopic Gastrostomy: A Case Series of 1041 Patients

Abstract: Cancer, cirrhosis and radiation therapy were predictors of infection. Post-PEG bleeding and other complications were rare events. Collectively, the data suggested that patients taking concurrent anticoagulants had no elevated risk of post-PEG bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 26 publications
4
50
1
13
Order By: Relevance
“…In the present study, no antibiotic prophylaxis was used, and the rate of peristomal infections observed in the present study was 2.3 %, lower than the rates (5-36 %) reported in earlier literature [19][20][21]. Risk factors include cancer, cirrhosis, radiation exposure, diabetes, the size of the tube, and experience [17][18][19][20][21][22].…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In the present study, no antibiotic prophylaxis was used, and the rate of peristomal infections observed in the present study was 2.3 %, lower than the rates (5-36 %) reported in earlier literature [19][20][21]. Risk factors include cancer, cirrhosis, radiation exposure, diabetes, the size of the tube, and experience [17][18][19][20][21][22].…”
Section: Discussioncontrasting
confidence: 64%
“…Out of five patients in the present study, the diagnosis was confirmed by endoscopy in two and Although reported complications associated with bleeding are frequent, the rate of such complications was relatively low in the present study. While the ESPEN guidelines recommend maintaining an INR of below 1.5 in order to reduce bleeding complications [7], in a study of 1041 patients, Richter-Schrag et al reported that the use of anticoagulants and increased INR values do not increase the rate of bleeding complications [22]. In the present study, the patients were provided with continuous anticoagulant treatment prior to the procedure but kept their INR level below 2.5.…”
Section: Discussionmentioning
confidence: 85%
“…The most common complication of PEG placement is peristomal wound infection, which occurs in approximately 11% within 1 week of placement. One recent study found the rate of peristomal wound infection to be significantly increased amongst patients with malignancy, cirrhosis, and radiation exposure [28]. One limitation of this study was that the provision of periprocedure prophylactic IV antibiotics was not universal, which is the current recommendation in North America.…”
Section: Introductionmentioning
confidence: 89%
“…Problem: high complication rate and 30-day mortality rate; solution -careful patient selection and use of a multidisciplinary enteral access service Even through society guidelines recommend against PEG placement in patients with an expected survival of less than 30 days, the short-term mortality following PEG placement remains relatively high, with a 30-day mortality rate of 5.8-6.5%, 60-day mortality rate of 10-18%, and 1-year mortality rate of 32-41% [28][29][30]. In a retrospective review of over 1000 patients undergoing PEG, predictors of 30-day mortality included: age over 56 years [odds ratio (OR) 1.04, 95% confidence interval (CI) 1.00-1.07], and diabetes mellitus (OR 4.45, 95% CI 1.33-13.01).…”
Section: Introductionmentioning
confidence: 99%
“…Minör komplikasyonlar olarak kabul edilen bu grup içinde en sık görülenler yara yeri enfeksiyonu ve katater kenarından sızdır-madır. Bizim çalışmamızda enfeksiyon en sık görülen komplikasyondur ve bazı durumlarda kateterin çekilmesini gerektirebilir [21]. Çalışmamızda 8(%8,2) hastada lokal yara yeri enfeksiyonu ve 2(%2,1) hastamızda tüp kenarından sızdırma olmuş ve basit antibiyotik tedavisi ile kontrol altına alınarak tüpün çekil- mesini gerektirecek bir durum izlenmemiştir.…”
Section: Gereç Ve Yöntemunclassified